2016
DOI: 10.1007/s00442-016-3705-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic constraints modify optimal photosynthetic profiles in giant sequoia trees

Abstract: Optimality theory states that whole-tree carbon gain is maximized when leaf N and photosynthetic capacity profiles are distributed along vertical light gradients such that the marginal gain of nitrogen investment is identical among leaves. However, observed photosynthetic N gradients in trees do not follow this prediction, and the causes for this apparent discrepancy remain uncertain. Our objective was to evaluate how hydraulic limitations potentially modify crown-level optimization in Sequoiadendron giganteum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 86 publications
1
23
2
Order By: Relevance
“…This means that the saturation vapor concentration over a surface of water potential zero (w i, 0 ) is 0.92 mol m −3 (Haynes, 2010 ). The realistic leaf water potential values can be assumed to vary from −0.5 to −2.2 MPa (Ambrose et al, 2016 ). It is difficult to assess what the actual value for stomatal conductance would be during such conditions due to the difficulty in measuring the actual stomatal conductance (see Figure 5A ) and also due to technical limitations of measuring small transpiration rates at high RH, when the transpiration may be also masked by condensation on the surfaces (e.g., Altimir et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…This means that the saturation vapor concentration over a surface of water potential zero (w i, 0 ) is 0.92 mol m −3 (Haynes, 2010 ). The realistic leaf water potential values can be assumed to vary from −0.5 to −2.2 MPa (Ambrose et al, 2016 ). It is difficult to assess what the actual value for stomatal conductance would be during such conditions due to the difficulty in measuring the actual stomatal conductance (see Figure 5A ) and also due to technical limitations of measuring small transpiration rates at high RH, when the transpiration may be also masked by condensation on the surfaces (e.g., Altimir et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Congruent with this idea, in an experiment in the tropical tree Moringa oleifera, Echeverría et al (2019) found that vessel diameter and number change with height growth in a way that maintained hydraulic conductance constant with leaf area. Some researchers, however, have documented drops in photosynthetic productivity and stomatal conductance with height growth (Koch et al, 2004;Ambrose et al, 2016). Maintaining constant (or increasing) conductance with height growth is likely especially important for forest tree species, which grow up through a dark and humid understory into much higher radiation environments with higher evaporative demand (Gleason et al, 2018b).…”
Section: What Is Selection Acting On In Favoring Tip-to-base Conduit mentioning
confidence: 99%
“…It has long been known that stomatal conductance is often systematically suppressed in upper‐canopy leaves (Ryan & Yoder, 1997; Delzon et al ., 2004; Koch et al ., 2004). Such suppression would cause optimal photosynthetic capacity to be lower than expected in the upper canopy (Peltoniemi et al ., 2012; Buckley et al ., 2013), and could arise from low leaf water potentials, caused either by the greater hydraulic resistance encountered in transporting water to more distal sites in the canopy, or by elevated evaporative demand in more sunlit locations (Ambrose et al ., 2016; Bachofen et al ., 2020). Indeed, stomatal conductance responds negatively both to reduced water potential and increased evaporative demand (Buckley, 2019).…”
Section: Introductionmentioning
confidence: 99%